Breast arterial calcification and epicardial adipose tissue volume, but not density are independently associated with cardiovascular risk. (1st August 2022) - Goel, Vinay; Spear, Ella; Cameron, William; Thakur, Udit; Sultana, Nushrat; Chan, Jasmine; Tan, Sean; Joshi, Mitwa; Roberts, Andrew; Cheen, Yeong Chee; Youn, Hannah; Dey, Damini; et al.
Abstract: Background: Mammographically detected breast arterial calcification (BAC) has been proposed as surrogate marker for coronary artery disease (CAD) in women. Epicardial adipose tissue (EAT) and peri-coronary adipose tissue (PCAT) are inflammatory fat depots linked to atherogenesis. BAC has demonstrated association with inflammation, therefore we aimed to determine the association between BAC, EAT and PCAT. Methods: Single-centre, retrospective, cross-sectional study of women with digital mammography and coronary computed tomography angiography (CCTA). EAT and PCAT were quantitively assessed using semi-automated software. Patient demographics and cardiovascular risk factors were obtained from medical records and mammograms reviewed for BAC. Pre-test cardiovascular risk was determined with CAD Consortium Score. Chi-square, t -test and Mann-Whitney U tests were used to assess between group differences. Multivariable linear and logistic regression modelling was conducted to adjust for confounders. Results: Among 153 patients (age 61, SD 11) included in this study, BAC was present in 37 (24%) patients. BAC-positive patients had higher EAT volume (EATv) (110.2 mL, SD 41 mL vs 94.4 mL, SD 41 mL, p  = 0.02) but this association was not significant after adjusting for cardiovascular risk factors ( p  = 0.26). BAC did not associate with EAT density or PCAT. BAC and EATv were strongly associated with cardiovascular risk and CAD independent of each other: CV risk (BAC OR 7.55 (3.26–18.49), p  < 0.001, EATv OR 1.02 (1.01–1.03), p < 0.001), CAD presence (BAC OR 4.26 (1.39–13), p  = 0.01; EATv OR 1.01 (1.0–1.03), p  = 0.04). Conclusion: BAC and EATv are independent predictors of CV risk and CAD, but don't independently associate with each other, the relationship confounded by shared cardiovascular risk factors. BAC doesn't appear to associate with adipose tissue density and its presence may be cumulative result of long-term exposure to CV risk factors. Highlights: BAC and EAT are not directly associated but both independently associate with CAD. BAC may be the result of cumulative long-term cardiac risk factor exposure. BAC positive patients have greater EAT volume.